2021
DOI: 10.3390/idr13030061
|View full text |Cite
|
Sign up to set email alerts
|

Viral Load Difference between Symptomatic and Asymptomatic COVID-19 Patients: Systematic Review and Meta-Analysis

Abstract: We conducted a systematic review and meta-analysis to investigate the possible difference in the SARS-CoV-2 viral load between asymptomatic and symptomatic COVID-19 patients. Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines were followed in abstracting data and assessing validity. We searched MEDLINE, Scopus, Web of Science and Google Scholar for all investigations in the English language, reporting data on the threshold cycle (Ct) from real-time RT-PCR assays for the RNA-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 25 publications
4
23
0
Order By: Relevance
“…Rapid PCR-based SARS-CoV-2 detection is particularly important in high-frequency testing settings which is often associated with asymptomatic routine testing at workplaces or schools. Our data demonstrate no difference in viral loads between the asymptomatic and symptomatic individuals (Figure 2B-C), in line with previous studies 28 . Several studies have also evaluated the use of RT loop-mediated isothermal amplification (RT-LAMP) in saliva samples for fast detection of SARS-CoV-2.…”
Section: Discussionsupporting
confidence: 93%
“…Rapid PCR-based SARS-CoV-2 detection is particularly important in high-frequency testing settings which is often associated with asymptomatic routine testing at workplaces or schools. Our data demonstrate no difference in viral loads between the asymptomatic and symptomatic individuals (Figure 2B-C), in line with previous studies 28 . Several studies have also evaluated the use of RT loop-mediated isothermal amplification (RT-LAMP) in saliva samples for fast detection of SARS-CoV-2.…”
Section: Discussionsupporting
confidence: 93%
“…Some meta analyses indicated no significant difference in viral load at the upper respiratory tract for symptomatic vs . asymptomatic individuals ( Walsh et al, 2020 ; Zuin et al, 2021 ), and levels of viral RNA in saliva are in general comparable to those found in NP swabs ( Butler-Laporte et al, 2021 ). This would suggest that the limit of detection of COV-ID matches and exceeds what is needed to detect viral RNA in saliva of infectious and potentially contagious individuals.…”
Section: Discussionmentioning
confidence: 55%
“…Similar findings have also been reported recently (28,29). In contrast, some studies found no difference in viral load between the two groups (30,31,) while others found higher viral load among asymptomatic individuals (32,33). Higher sensitivity has been observed among individuals presenting in the early symptomatic phase of their infection (12,22,2527,3436).…”
Section: Discussionmentioning
confidence: 86%